5/2y^2+6y – 4y-3y^3/y^3-9y -3

5/2y^2+6y – 4y-3y^3/y^3-9y -3

2 bình luận về “5/2y^2+6y – 4y-3y^3/y^3-9y -3”

  1. Giải đáp:
     \frac{5}{2y^{2}+6y}-\frac{4y-3y^{3}}{y^{3}-9y}-3 (đk: y\ne0;y\ne\pm3)
    =\frac{5}{2y.(y+3)}-\frac{4y-3y^{3}}{y.(y^{2}-9)}-3
    =\frac{5.(y-3)}{2y.(y^{2}-9)}-\frac{(4y-3y^{3}).2}{2y.(y^{2}-9)}-\frac{3.2y.(y^{2}-9)}{2y.(y^{2}-9)}
    =\frac{5y-15-8y+6y^{3}-6y.(y^{2}-9)}{2y.(y^{2}-9)}
    =\frac{6y^{3}-3y-15-6y^{3}+54y}{2y.(y^{2}-9)}
    =\frac{51y-15}{2y.(y^{2}-3^{2})}
    =\frac{51y-15}{2y.(y-3).(y+3)}

    Trả lời
  2. Đáp án + giải thích các bước giải:
    Gửi ạ
    5/(2y^{2}+6y) – (4y-3y^{3})/(y^{3}-9y) -3
    = 5/(2y(y+3)) – (4y-3y^{3})/(y(y^{2}-9)) -3
    = (5(y-3))/(2y(y+3)(y-3)) – (2(4y-3y^{3}))/(2y(y-3)(y+3)) -(6y(y-3)(y+3))/(2y(y+3)(y-3))
    = (5y-15-8y+6y^{3}-6y^{3}+54y)/(2y(y+3)(y-3))
    = (51y-15)/(2y(y^{2}-9))
    = (51y-15)/(2y^{3}-18y)

    Trả lời

Viết một bình luận

Câu hỏi mới